Guest editorial: Special issue on integration of IoT with future Internet - Pathan, Al-Sakib Khan; Saeed, Rashid Abdelhaleem; Feki, Mohamed Ali; Tran, Nguyen H. (Taiwan Academic Network, Ministry of Education, Taipei, Taiwan, ROC, 2014)
The Internet of Things (IoT) is the terminology used for uniquely identifiable objects (or, things) and their virtual representations in an Internet-like structure.